EEG abnormalities and seizures in genetically diagnosed Fragile X syndrome. Issue 38 (9th July 2014) - Heard, Takijah T.; Ramgopal, Sriram; Picker, Jonathan; Lincoln, Sharyn A.; Rotenberg, Alexander; Kothare, Sanjeev V.
Abstract: We describe the seizure and EEG characteristics in a population of children with known Fragile X. The medical records of 135 genetically confirmed FXS patients receiving care in a Fragile X clinic and their available EEG reports were reviewed. The mean age was 5.94 years old including 18 males and 1 female. The mean age was 4–9 years old with an age range of 15 months to 13 years old. Twenty‐two patients (16.3%) in the series had parent‐reported behavior suspicious of seizures. Sixteen patients (14.1%, 1 female) had at least one EEG recorded for evaluation of clinical events suspicious for seizure, and three patients (2.2%) had an EEG in the context of a polysomnography for diagnosing sleep apnea. The mean age at EEG evaluation was 6.0 years (standard deviation 3.8 years). EEG findings included slowing of background rhythm ( n = 9) and epileptiform discharges ( n = 7). Four patients had normal EEGs ( n = 4). Six patients (4.4% of the sample population) were diagnosed with epilepsy by both clinical seizure semiology and documented EEG abnormalities. Thirteen patients (68.4% of total) had episodes of staring and behavioral arrest with no EEG correlate, indicating non‐epileptic events. Of the eight patients who underwent a repeat EEG, five patients had showed normalization in the posterior dominant rhythm over time, two patients had unchanged findings and one patient had worsening of his EEG. Our data warrant further prospective validation.